Pulmonary Hypertension Complicating Connective Tissue Disease - Lynch, Joseph P., III; Belperio, John A.; Saggar, Rajeev; Fishbein, Michael C.; Saggar, Rajan (Seminars in Respiratory and Critical Care Medicine, 2013)
Pulmonary hypertension (PH) may complicate connective tissue disease (CTD), particularly systemic sclerosis (SSc, scleroderma), and markedly increases mortality. More than 70% of cases of PH complicating CTD occur in SSc, which is the major focus of this article. Pulmonary complications (i.e., interstitial lung disease [ILD] and PH) are the leading causes of scleroderma-related deaths. “Isolated” PH (i.e., without ILD) complicates SSc in 7.5 to 20% of cases; secondary PH may also occur in patients with SSc-associated ILD. Several clinical markers and specific autoantibody profiles have been associated with PH in SSc. The role of PH-specific therapy is controversial, as prognosis and responsiveness to therapy are worse in SSc-associated PH compared with idiopathic pulmonary arterial hypertension. We discuss medical therapies for CTD-associated PH and the role of lung transplantation for patients failing medical therapy.
Keywords: systemic sclerosis; scleroderma; pulmonary hypertension; pulmonary arterial hypertension; connective tissue disease